Chemical Inhomogeneity, Short‐Range Order, and Magnetism in the LiNiO2‐NiO Solid Solution. Issue 43 (13th September 2013) - Barton, Phillip T.; Premchand, Y. Daniel; Chater, Philip A.; Seshadri, Ram; Rosseinsky, Matthew J.
Abstract NiO:Li is an early exemplar for which hole‐doping of a correlated insulator gives rise to rich and varied magnetic behavior. It is also an important system from the viewpoint of p‐type transparent conducting oxides, and is representative of a large class of materials that have been used in lithium ion batteries, since the end‐member compound, LiNiO2, belongs to the class of layered cathode materials. Despite the deceptive structural and compositional simplicity of this system, a complete understanding of its complex magnetic properties has remained elusive. Here a comprehensive investigation of the solid solution LixNi2−xO2, examining samples of precise stoichiometry using a combination of high‐resolution synchrotron X‐ray powder diffraction and SQUID magnetometry, is provided. The focus is on the interesting region between 0.40<x<1.00 in which the magnetic ordering temperature changes drastically with composition. The magnetism evolves from strong G‐type antiferromagnetism of x=0.40 with TN=327 K to robust uncompensated magnetic order at TN=240 K when x is close to 0.7, and to glassy A‐type antiferromagnetism of x=1.00 at TN=9 K. This study demonstrates this magnetic behavior is linked to the Li–Ni chemical order that develops from short‐ to long‐range. The interfaces between ordered domains give rise to magnetic exchange bias, which manifests as a shift in the magnetization‐field loop for samples with nanoscale coherence lengths (0.54<x<0.66).